\(x^2\left(x-1\right)-4x^2+8x-4=0\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 10 2019

\(x^2\left(x-1\right)-4x^2+8x-4=0\)

\(x^2\left(x-1\right)-4\left(x^2-2x+1\right)=0\)

\(x^2\left(x-1\right)-4\left(x-1\right)^2=0\)

\(\left(x-1\right)\left(x^2-4x+4\right)=0\)

\(\left(x-1\right)\left(x-2\right)^2=0\)

\(\Rightarrow\orbr{\begin{cases}x-1=0\\\left(x-2\right)^2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=1\\x=2\end{cases}}\)

15 tháng 10 2019

\(x^2\left(x-1\right)-4x^2+8x-4=0\)

<=> \(x^3-x^2-4x^2+8x-4=0\)

<=> \(x^3-5x^2+8x-4=0\)

<=>\(x^3-x^2-4x^2+4x+4x-4=0\)

<=>\(x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)=0\)

<=>\(\left(x-1\right)\left(x^2-4x+4\right)=0\)

<=>\(\left(x-1\right)\left(x-2\right)^2=0\)

<=>\(\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}}\)<=>\(\orbr{\begin{cases}x=1\\x=2\end{cases}}\)

Vậy \(\orbr{\begin{cases}x=1\\x=2\end{cases}}\) 

27 tháng 6 2017

a) ... \(\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\)

\(\Leftrightarrow\left(x-1\right)\left(x-2\right)\left(x+2\right)=0\Leftrightarrow\hept{\begin{cases}x=1\\x=2\\x=-2\end{cases}}\)Vậy.....

b) ... \(\Leftrightarrow x^3\left(x-2\right)+10x\left(x-2\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(x^3+10x\right)=0\)

\(\Leftrightarrow x\left(x-2\right)\left(x^2+10\right)=0\Leftrightarrow\hept{\begin{cases}x=0\\x=2\\x^2=-10\Rightarrow x\in\theta\end{cases}}\)(\(\theta\)là rỗng) Vậy.........

c) ... \(\Leftrightarrow2x-3=x+5\Leftrightarrow x=8\)Vậy.......

d) ... \(\Leftrightarrow x\left(x^2-16\right)=0\Leftrightarrow x\left(x-4\right)\left(x+4\right)=0\Leftrightarrow\hept{\begin{cases}x=0\\x=4\\x=-4\end{cases}}\)Vậy......

17 tháng 10 2016

a) \(x^3-16x=0\)

\(\Leftrightarrow x\left(x^2-16\right)=0\)

\(\Leftrightarrow x\left(x-4\right)\left(x+4\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x-4=0\\x+4=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x=4\\x=-4\end{array}\right.\)

b) \(\left(2x-3\right)^2=\left(x-5\right)^2\)

\(\Leftrightarrow\left(2x-3\right)^2-\left(x-5\right)^2=0\)

\(\Leftrightarrow\left(2x-3+x-5\right)\left(2x-3-x+5\right)=0\)

\(\Leftrightarrow\left(3x-8\right)\left(x+2\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x=2\\x=\frac{8}{3}\end{array}\right.\)

c) \(x^2\left(x-1\right)-4x^2+8x-4=0\)

\(\Leftrightarrow x^2\left(x-1\right)-4\left(x^2-2x+1\right)=0\)

\(\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\)

\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x=1\\x=2\end{array}\right.\)

17 tháng 10 2016

có cần " vậy " k ?

 

1 tháng 10 2020

a) (2x - 3)2 = (x + 5)2

=> 4x2 - 12x + 9 = x2 + 10x + 25

=> 4x2 - 12x + 9 - (x2 + 10x + 25) = 0

=> 3x2 - 22x - 16 = 0

=> 3x2 - 24x + 2x - 16 = 0

=> 3x(x - 8) + 2(x - 8) = 0

=> (3x + 2)(x - 8) = 0

=> \(\orbr{\begin{cases}3x+2=0\\x-8=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-\frac{2}{3}\\x=8\end{cases}}\)

b) x2(x - 1) - 4x2 + 8x - 4 = 0

=> x2(x - 1) - (2x  - 2)2 = 0

=> x2(x - 1) - [2(x- 1)]2 = 0

=> x2(x - 1) - 4(x - 1)2 = 0

=> (x - 1)(x2 - 4(x - 1) = 0

=> (x - 1)(x2 - 4x + 4) = 0

=> (x - 1)(x - 2)2 = 0

=> \(\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}\)

c) x2 + 7x + 12 = 0

=> x2 + 3x + 4x + 12 = 0

=> x(x + 3) + 4(x + 3) = 0

=> (x + 4)(x + 3) = 0

=> \(\orbr{\begin{cases}x+4=0\\x+3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-4\\x=-3\end{cases}}\)

d) x2 + 3x - 18 = 0

=> x2 + 6x - 3x - 18 = 0

=> x(x + 6) - 3(x + 6) = 0

=> (x - 3)(x + 6) = 0

=> \(\orbr{\begin{cases}x-3=0\\x+6=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=-6\end{cases}}\)

e) x(x + 6) - 7x - 42 = 0

=> x(x + 6) - 7(x + 6) = 0

=> (x - 7)(x + 6) = 0

=> \(\orbr{\begin{cases}x-7=0\\x+6=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=7\\x=-6\end{cases}}\)

1 tháng 10 2020

1. ( 2x - 3 )2 = ( x + 5 )2

<=> ( 2x - 3 )2 - ( x + 5 )2 = 0

<=> [ ( 2x - 3 ) - ( x + 5 ) ][ ( 2x - 3 ) + ( x + 5 ) ] = 0

<=> ( 2x - 3 - x - 5 )( 2x - 3 + x + 5 ) = 0

<=> ( x - 8 )( 3x + 2 ) = 0

<=> \(\orbr{\begin{cases}x-8=0\\3x+2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=8\\x=-\frac{2}{3}\end{cases}}\)

2. x2( x - 1 ) - 4x2 + 8x - 4 = 0

<=> x2( x - 1 ) - ( 4x2 - 8x + 4 ) = 0

<=> x2( x - 1 ) - 4( x2 - 2x + 1 ) = 0

<=> x2( x - 1 ) - 4( x - 1 )2 = 0

<=> ( x - 1 )[ x2 - 4( x - 1 ) ] = 0

<=> ( x - 1 )( x2 - 4x + 4 ) = 0

<=> ( x - 1 )( x - 2 )2 = 0

<=> \(\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}\)

3. x2 + 7x + 12 = 0

<=> x2 + 3x + 4x + 12 = 0

<=> x( x + 3 ) + 4( x + 3 ) = 0

<=> ( x + 3 )( x + 4 ) = 0

<=> \(\orbr{\begin{cases}x+3=0\\x+4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-3\\x=-4\end{cases}}\)

4. x2 + 3x - 18 = 0

<=> x2 - 3x + 6x - 18 = 0

<=> x( x - 3 ) + 6( x - 3 ) = 0

<=> ( x - 3 )( x + 6 ) = 0

<=> \(\orbr{\begin{cases}x-3=0\\x+6=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=-6\end{cases}}\)

5. x( x + 6 ) - 7x - 42 = 0

<=> x( x + 6 ) - 7( x + 6 ) = 0

<=> ( x + 6 )( x - 7 ) = 0

<=> \(\orbr{\begin{cases}x+6=0\\x-7=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-6\\x=7\end{cases}}\)

25 tháng 6 2018

\(x^3+9x=0\)

<=> \(x\left(x^2+9\right)=0\)

<=> \(\orbr{\begin{cases}x=0\\x^2+9=0\end{cases}}\)

<=> \(\orbr{\begin{cases}x=0\\x\in\varnothing\end{cases}}\)

<=> \(x=0\)

\(9x^2-4-2\left(3x-2\right)^2=0\)

<=> \(\left(9x^2-4\right)-2\left(3x-2\right)^2=0\)

<=> \(\left[\left(3x\right)^2-2^2\right]-2\left(3x-2\right)^2=0\)

<=> \(\left(3x-2\right)\left(3x+2\right)-2\left(3x-2\right)^2=0\)

<=> \(\left(3x-2\right)\left[\left(3x+2\right)-2\left(3x-2\right)\right]=0\)

<=> \(\left(3x-2\right)\left(3x+2-6x+4\right)=0\)

<=> \(\left(3x-2\right)\left(-3x+6\right)=0\)

<=> \(\left(3x-2\right)3\left(-x+2\right)=0\)

<=> \(3\left(3x-2\right)\left(2-x\right)=0\)

<=> \(\orbr{\begin{cases}3x-2=0\\2-x=0\end{cases}}\)

<=> \(\orbr{\begin{cases}3x=2\\x=2\end{cases}}\)

<=> \(\orbr{\begin{cases}x=\frac{2}{3}\\x=2\end{cases}}\)

\(\left(x^3-x^2\right)-4x+8x-4=0\)

<=> \(\left(x^3-x^2\right)+\left(4x-4\right)=0\)

<=> \(x^2\left(x-1\right)+4\left(x-1\right)=0\)

<=> \(\left(x-1\right)\left(x^2+4\right)=0\)

<=> \(\orbr{\begin{cases}x-1=0\\x^2+4=0\end{cases}}\)

<=> \(x=1\)

\(\left(25x^2-10x\right):\left(-5x\right)-3\left(x-2\right)=4\)

<=> \(5x\left(5x-2\right)\left(-\frac{1}{5x}\right)-3\left(x-2\right)=4\)

<=> \(-\left(5x-2\right)-3\left(x-2\right)=4\)

<=> \(\left(5x-2\right)+3\left(x-2\right)=-4\)

<=> \(5x-2+3x-6=-4\)

<=> \(8x-8=-4\)

<=> \(8\left(x-1\right)=-4\)

<=> \(x-1=-\frac{1}{2}\)

<=> \(x=-\frac{3}{2}\)

27 tháng 10 2018

\(a,x\left(8x-2\right)-8x^2+12=0\)

\(\Rightarrow8x^2-2x-8x^2+12=0\)

\(\Rightarrow-2x+12=0\)

\(\Rightarrow-2x=-12\)

\(\Rightarrow x=6\)

\(b,x\left(4x-5\right)-\left(2x+1\right)^2=0\)

\(\Rightarrow4x^2-5x-4x^2-4x-1=0\)

\(\Rightarrow-9x-1=0\)

\(\Rightarrow-9x=1\)

\(\Rightarrow x=\frac{-1}{9}\)

27 tháng 10 2018

a) x(8 - 2) - 8x2 + 12 = 0

x(8 - 2) - 8x2 = 12 - 0

x(8 - 2) - 8x2 = 12

2x = 12

x = 6

b) x(4x - 5) - (2x + 1)= 0

9x - 1 = 0

9x = 0 + 1

9x = 1

x = -1/9

26 tháng 2 2022

hic, mk chx học

9 tháng 6 2017

a) \(4x^2-8x=0\)

\(\Rightarrow4x\left(x-2\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}4x=0\\x-2=0\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=0+2\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)

Vậy \(x_1=0;x_2=2\)

b) \(\left(x+5\right)-3x\left(x+5\right)=0\)

\(\Rightarrow-3x^2-14x+5=0\)

\(\Leftrightarrow\left(-3x+1\right)\left(x+5\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}-3x+1=0\\x+5=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{1}{3}\\x=-5\end{matrix}\right.\)

Vậy \(x_1=-5;x_2=\dfrac{1}{3}\)

9 tháng 6 2017

\(a,4x^2-8x=0\Rightarrow4x\left(x-8\right)=0\Rightarrow\left[{}\begin{matrix}4x=0\\x-8=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=8\end{matrix}\right.\)\(b,\left(x+5\right)-3x\left(x+5\right)=0\Leftrightarrow\left(x+5\right)\left(1-3x\right)=0\Rightarrow\left[{}\begin{matrix}x+5=0\\1-3x=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-5\\3x=1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-5\\x=\dfrac{1}{3}\end{matrix}\right.\)